Nanomolar clodronate induces adenosine accumulation in the perfused rat mesenteric bed and mesentery-derived endothelial cells - Donoso, M. Verónica; Hernández, Felipe; Barra, Rafael; Huidobro-Toro, J. Pablo (Frontiers in Pharmacology, 2023)
The vesicular nucleotide transporter (VNUT) is critical for sympathetic co-transmission and purinergic transmission maintenance. To examine this proposal, we assessed whether the bisphosphonate clodronate, claimed as a potent in vitro VNUT blocker, modified spontaneous and/or the electrically evoked overflow of ATP/metabolites and NA from mesentery sympathetic perivascular nerve terminals. Additionally, in primary endothelial cell cultures derived from this tissue, we also evaluated whether clodronate interfered with ATP/ metabolites cell outflow, metabolism of N6-etheno adenosine 5’-triphosphate (eATP), N6-etheno adenosine (eADO) and adenosine deaminase enzyme activity. Rat mesenteries were perfused in the absence or presence of 0.01-1000 nM clodronate, 1-1000 nM Evans blue (EB), 1-10 µM DIDS; tissue perfusates were collected to determine ATP/metabolites and NA before, during and after perivascular electrical nerve terminals depolarization. 1-1000 nM clodronate did not modify the time course of ATP or NA overflow elicited by nerve terminals depolarization, only 10 nM clodronate significantly augmented perfusate adenosine. Electrical nerve terminals stimulation increased tissue perfusion pressure that was significantly reduced only by 10 nM chlodronate (90.0±18.6 (n=8) to 35.0± 10.4 (n=7), p=0.0277). As controls, EB, DIDS or reserpine treatment reduced in a concentration-dependent manner the overflow of ATP/metabolites and NA elicited by nerve terminals depolarization. Moreover, mechanical stimulation of primary endothelial cell cultures from the rat mesentery added with 10 or 100 nM clodronate increased adenosine in the cell media. eATP was metabolized by endothelial cells to the same extent with and without 1-1000 nM clodronate, suggesting the bisphosphonate did not interfere with nucleotide ectoenzyme metabolism. In contrast, extracellular eADO, remained intact, and indication that this nucleoside is not metabolized nor transported intracellularly. Furthermore, only 10 nM clodronate inhibited (15.5%) adenosine metabolism to inosine in endothelial cells as well as in a commercial crude adenosine deaminase enzyme preparation (12.7%) both effects proved significant (p<0.05). Altogether, present data allows to infer that clodronate inhibits adenosine deaminase activity in isolated endothelial cells as in a crude extract preparation, a finding that may account for adenosine accumulation following clodronate mesentery perfusion.